Is there a vascular side of the story? Vascular consequences during COVID‐19 outbreak in Lombardy, Italy. Issue 5 (4th October 2020) - Bissacco, Daniele; Grassi, Viviana; Lomazzi, Chiara; Domanin, Maurizio; Bellosta, Raffaello; Piffaretti, Gabriele; Trimarchi, Santi
Abstract: Background: Lombardy, in the northern Italy, was one of the most affected region in the world by novel coronavirus COVID‐19 outbreak. Due to the dramatic amount of confirmed positive cases and deaths, all clinical and surgical hospital departments changed their daily activities to face emergent pandemic situations. In particular, vascular surgery units reorganized their role and priorities for both elective and urgent patients requiring open or endovascular interventions. Material & Methods: This brief review summarizes organization of vascular Lombardy centers network adopted during pandemic period and clinical evidences published so far by regional referral and nonreferral hospitals in terms of vascular surgery and medicine implications in COVID‐19 positive or negative patients managements. Results: Different patterns of disease were described during phase 1 COVID‐19 outbreak in Lombardy region, with major attention in pheriperal artery disease and venous thrombosis. Conclusion: COVID‐19 infection seems to be not only a pulmonary but also a vascular (arterial and venous) disease. Further study are necessary to described mid and long‐term outcomes in COVID‐19 vascular patients population.